Self-efficacy assessment in chemistry learning: Development and validation using confirmatory factor analysis - Jajang Muhariyansah; Hari Sutrisno; Fajar Naqsyahbandi (Jurnal Pendidikan Kimia (JPKIM), 2023)
Learner self-efficacy is the confidence of a learner to determine how he feels, thinks, motivates and behaves. The purpose of this study was to analyze the instrument of self-efficacy assessment of students in the Aliyah madrasah in Musi Rawas Prov. South Sumatra. The total of respondents to testing this instrument was 234 students. This study uses Second Order Confirmatory Factor Analysis (CFA) to determine the validity and reliability of Likert scale instruments regarding students' self-efficacy in chemistry learning. The sampling technique used is proportionate Stratified Random Sampling. The research results show that the instrument developed has good construct validity as seen from the loading factor value > 0.50. The construct reliability test using CR and AVE values also showed acceptable results so it was declared suitable for use in data collection to measure self-efficacy in learning chemistry. It is hoped that teachers can measure student self-efficacy using this instrument. It is expected that teachers can measure students' self-efficacy using this instrument.Keywords: Assesment; Confirmatory factor analysis; Development; Self-efficacy